Cinematic Kathmandu: imaginaries of the city - Karki, Dikshya (2021)
This thesis is an analysis of the relationship between the imagined and material city of Kathmandu as represented in films. It centers on the main argument that cities from the Global South and those in the periphery such as Kathmandu can be studied as cinematic cities. By analyzing the screen depictions of migration and urbanization in Kathmandu, this study proposes to understand ‘new Nepali cinema’ as ‘urban popular’ films. However, the twin tropes of maulikatā and nepālīpana attached to ‘new Nepali cinema’ complicate its understanding. These arguments are derived from visual and textual analysis, qualitative interviews, and participant observation. The study also locates the architectural identifiers of Kathmandu and analyses the screen images of Nepali women in films. Furthermore, it traces the history and patterns of film viewing practices in Kathmandu’s cinema halls, multiplexes, film festivals, and digital platforms. This research seeks to address the gap in the study of cinematic cities which is currently dominated by literature on cities from the Global North.